Risk factors associated with dengue hemorrhagic fever incidence in the Belawan II Community Health Center - Sari, Juwita Purnama; Ginting, Rapael; Sihotang, Widya Yanti; Fioni, Fioni; Tarigan, Antje Irmella; Malau, Reghita Claudia; Angkasa, Alexander; Lizar, Budi Septhian (Buletin Kedokteran & Kesehatan Prima, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern in tropical regions such as Indonesia, where environmental and behavioural factors play crucial roles in its transmission. This study aimed to analyse the factors associated with the incidence of DHF in the working area of the Belawan II Community Health Centre in Medan. A quantitative approach with a cross-sectional design was employed. A sample of 110 housewives was selected via purposive sampling from a population of 150 housewives in the area. Data were collected through questionnaires and observation, then analysed using univariate, bivariate (Chi-Square test), and multivariate (logistic regression) methods. Bivariate analysis revealed significant associations between DHF incidence and the following factors: education level (p=0.001), housewives' knowledge (p=0.000), 3M Plus behaviour (p=0.000), health promotion services (p=0.000), and the presence of mosquito larvae (p=0.000). In contrast, variables for age (p=0.161) and occupation (p=0.898) showed no significant association. Multivariate analysis identified health promotion services as the dominant factor associated with DHF incidence (OR=0.029; 95% CI=0.010-0.084; p=0.000), with housewives' knowledge serving as a supporting factor. In conclusion, DHF prevention efforts in the Belawan II area should prioritise enhancing the quality and coverage of effective health promotion services, complemented by improving household-level knowledge and preventive practices, alongside sustainable control of mosquito breeding sites.